Knowledge of the interprofessional team about child autism (Research, Society and Development, 2019)
Autism is characterized as a neurodevelopmental syndrome, and many individuals who are diagnosed with autism present ineffective communication, and their movements, activities and interests are more repetitive, and have more aggressive behavior. The autistic has many characteristics, such as lack of social interaction, difficulties in maintaining relationships with other people and with their own family, end up isolating themselves and living their world and not realizing the reality that surrounds them. The objective was to analyze the knowledge of the interprofessional team about autistic disorder. This is an exploratory, descriptive study with a qualitative approach that used as a technical procedure data collection and cross-sectional field study. For analysis of the data was through the analysis of content of Bardin. The results showed that most of the professionals consider autism as a neurological disorder, with impairment in communication and social interaction, 90% of the participants have already cared for the autistic being highlighted the lack of preparation for attendance, lack of interprofessional interaction and the parents' unpreparedness for care. The stimulation of the child for its development was emphasized as an important factor. We conclude that it is fundamental that the interprofissioanl team has an effective relationship and helps and accompanies the child as well as the family in each situation lived, observing the family structure.